Water Resources and Military Dictatorship in Brazil - Martinez, Paulo Henrique [UNESP] (FapUNIFESP (SciELO), 2024)
Examination of public policies in the management of water resources in the state of São Paulo, during the government of Paulo Egydio Martins, between the time frames of the international oil crises (1973-1979). The sources are of a governmental nature, such as development plans, thematic reports from technical bodies, public companies and secretariats, programs, proposals and reports from managers and statements from the governor of São Paulo. The political actions carried out during the period were aimed at building and maintaining the political legitimacy of the military governments in the initial phase of the “ transition”, led by the military dictatorship, its representatives and civilian allies, in the legislative branches and in civil society. The following were highlighted: social and political relations supporting economic modernization through state planning under the slogan of Development with Security; the constant instability of the political legitimacy of the federal and state governments; the role of technical reason in containing and directing social change in Brazil.
Recursos Hídricos e Ditadura Militar no Brasil
Keywords: Environment; Health; Water